Il diritto del minore alla bigenitorialità nella giurisprudenza della Corte europea dei diritti (Società e diritti, 2021)
AbstractAfter identifyng the main international legal sources for the protection of the child, this work deals with analyzing the concept of best interest resulting from the decisions delivered by the European Court of human rights in the matter of divorce. This allows further reflections on the concept of biparentality and its use in the judgements of national